PENGARUH ASIMETRI INFORMASI, LEVERAGE DAN PERGANTIAN CHIEF EXECUTIVE OFFICER PADA PRAKTIK MANAJEMEN LABA - Wiasa Putri, Yura Karlinda; Widanaputra, Agung (E-Jurnal Akuntansi, 2015)
Definitions of earnings management company managers attempt to intervene or influence  information in the financial statements for purpose of deceiving the stakeholders who want to know the performance and condition of the company. The occurrence of earnings management can be influenced by several factors: asymmetry of information, leverage and turn the chief executive officer (CEO). This study aimed to determine the effect of information asymmetry, leverage and turn Chief Executive Officer (CEO) on earnings management practices companies listed on the Stock Exchange. The data used in this study were obtained from published financial statements of companies listed on the Stock Exchange from the year 2010-2013 with a sample of 56 companies observations. The data analysis technique used is multiple linear regression. Based analysis showed that partial information asymmetry and leverage positive effect on earnings management while turnover Chief Executive Officer (CEO) is a negative effect on earnings management.
Keywords: Asymmetry of information, leverage, CEO turnover, profit management